Actualization Of Islamic Education Values In Qs. Al-Fatihah In Islamic Learning - Zainudin Zainudin (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Technological developments, as well as changes in how people view the world of education, cause education of the modern era to experience degradation in terms of value. Especially in Islamic education, the religious values that are one of the core characteristics of Islamic teaching have decreased slightly to suffer a significant decline. This article aims to restore the principles and values of Islamic education through learning Islamic religion by making Surah al-Fatihah the primary source of information to explain the elements of the value of education that should be possessed by every education and student to reflect the religious aspects in the process of learning Islam. This qualitative research uses the research library method, using descriptive analysis. The research results show that some values of Islamic education are contained in Qs. Al-Fatihah, among others: Religious values, Always grateful, Polite, easy to forgive, hard work, not easy to despair, please help, always diligent in teaching science. The implication of Islamic education in the letter of Al-Fatihah in the world of education is that an educator and student must stick to the code of ethics of teachers and students.